KAJIAN LITERATUR : STRATEGI SEKOLAH TINGGI ILMU EKONOMI BIMA DALAM MENUMBUHKEMBANGKAN KEWIRAUSAHAAN DI KALANGAN MAHASISWA - Muniarty, Puji; M Rimawan; Ovriyadin, Ovriyadin; Ni Made Dwi Puspitawati (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Sekolah Tinggi Ilmu Ekonomi Bima is a private university in Bima City, West Nusa Tenggara which has a vision, namely to make the Sekolah Tinggi Ilmu Ekonomi Bima (STIE) an educational institution that produces superior, professional and enthusiastic human resources.Entrepreneurship. This research is about higher education strategies for developing entrepreneurship, especially management study program students with a focus on the main problems discussed, namely (1) The concept of entrepreneurship, (2) Factors that cause entrepreneurial success and failure, (3)Digital Preneur of students and (4) Strategies to foster entrepreneurship among students. This research uses the methodliterature review.The research sample read various references quoted from various books, journals and other publications that were relevant to the research content. Data was collected using library research data collection techniquessearching keyword article to be inreview with secondary data sources from google scholar and various published journal links according to the research referred to. The strategy of the College of Economics in developing entrepreneurship among students is through a) entrepreneurship supporting courses in the curriculum such as Introduction to Business, Entrepreneurship I, Entrepreneurship II,Digital Marketing, Cooperative & MSME Management, Creative Business Planning, Business Ethics and Event Management, (b) Establishing cooperation with domestic and foreign universities, provincial governments, city/district governments, banking, BUMN, and MSMEs as well as KKNT-MBKM ( c) Establishment of a Business Incubator and (d) Implementation of Entrepreneurial Fair Entrepreneurship Bazaar activities.